2020
DOI: 10.21203/rs.3.rs-68436/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential response to intravitreal dexamethasone implant in naïve and previously treated diabetic macular edema eyes

Abstract: Background: To identify different response patterns to intravitreal dexamethasone implants (IDI) in naïve and previously treated (PT) diabetic macular edema (DME) eyes in a real-life setting.Methods: 342 IDI injections (203 DME eyes) were included. Number of IDI injections, percentage (%) of eyes with 1, 2, 3 and ³ 4 injections, time to reinjections, visual acuity (VA), intraocular pressure (IOP) and central retinal thickness (CRT) were evaluated for naïve and PT DME eyes over 24 months.Results: Mean number of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…A few studies have evaluated treatment outcomes of dexamethasone implant for DMO in routine clinical practice after 12 months from the start of treatment [9,12,13,22]. These studies have reported a mean VA gain ranging from ?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have evaluated treatment outcomes of dexamethasone implant for DMO in routine clinical practice after 12 months from the start of treatment [9,12,13,22]. These studies have reported a mean VA gain ranging from ?…”
Section: Discussionmentioning
confidence: 99%
“…The intravitreal bevacizumab vs. intravitreal dexamethasone for DMO (BEV-ORDEX) study found that the proportion of eyes with vision improvement at 12 months was similar in the two groups from a mean number of injections of 2.7 in the dexamethasone and 8.6 in the bevacizumab group [8]. Some studies that reported the outcomes of the dexamethasone implant for DMO in routine clinical practice found that the implant was safe and effective in improving visual acuity and reducing macular thickness from a few injections [9][10][11][12][13]. This study aimed to report visual acuity, anatomic outcomes, proportion of eyes that received dexamethasone implant and the number of dexamethasone implants over the first year of treatment in eyes with DMO in routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, dexamethasone may cause high intraocular pressure with almost 22% of the patients exhibiting elevated pressure requiring medical treatment, as well as cataract progression. These adverse events may necessitate more frequent care and close monitoring among highrisk patients (Gillies et al 2014;Shah & Heier 2016;He et al 2018;Zarranz-Ventura et al 2020). Our sensitivity analysis found that at our baseline bevacizumab frequency of care or lower, beyond 3 dexamethasone visits increased the cost of annual treatment on average in both patient groups.…”
Section: Discussionmentioning
confidence: 77%
“… 2018 ; Zarranz‐Ventura et al. 2020 ). Our sensitivity analysis found that at our baseline bevacizumab frequency of care or lower, beyond 3 dexamethasone visits increased the cost of annual treatment on average in both patient groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation